O024 Trichomonas vaginalis – treatment and test of cure analysis in a GUM clinic population. (30th June 2016) - Bathgate, Gabriella; Perry, Melissa; White, John
Abstract : Background/introduction: Trichomonas vaginalis is prevalent in patients of black ethnicity in our south London population. Nucleic acid amplification testing (NAAT) is the diagnostic gold standard, and first-line treatment with metronidazole or tinidazole regimens thought to achieve comparable cure rates >90%. Test of cure (TOC) is recommended if symptoms persist following treatment, but this overlooks persistent asymptomatic infection and optimal timing and testing modality are uncertain. Aim(s)/objectives: To estimate clinical cure and TV eradication rates in a large cohort of T. vaginalis cases. Methods: All positive T. vaginalis NAAT results (TV TMA, Hologic) were identified between January 2013 and September 2015. Data were collected from our electronic patient record system, including clinical features, treatment regimen and TOC results, if performed. Results: 557 cases were identified in 500 patients (78.2% female; 82.2% Black African/Caribbean/mixed ethnicity; 8.8% HIV+). Infection was symptomatic in 47.3% (53.7% females, 24.5% males). Baseline wet mount microscopy was positive in 65.6%.TOC was performed in 72.4% (median time to TOC 4.1 weeks, IQR 2.3–7.6 weeks). 77.2% demonstrated parasitological clearance following a single treatment course. Cure rates were 70–80 for all regimens, significantly higher in males (85.5% vs 66.9%, p < 0.01). Discussion/conclusion: We see a significant asymptomatic, microscopy-negative burden of T. vaginalis infection. Lower clearance rates in women suggest azole-resistant strains may be prevalent. Based on NAAT results, cure rates are lower than expected, and relatively constant TMA positivity rate beyond 2 weeks suggests treatment failure is responsible rather than re-infection or timing of TOC. Further UK studies on treatment efficacy and molecular epidemiology are warranted.